2020
DOI: 10.1186/s12991-020-00271-w
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of attention-deficit/hyperactivity disorder (ADHD) in children and adolescents in Africa: a systematic review and meta-analysis

Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) is the most common neurodevelopmental disorders in childhood and adolescence, affecting 2.2 to 17.8% of all school-aged children and adolescents. ADHD in children has been associated with a wide range of developmental deficits including limitations of learning or control of executive functions as well as global impairments of social skills. However, no review has been conducted to report the consolidated magnitude of ADHD in children and adolescents i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 45 publications
4
41
0
3
Order By: Relevance
“…Specifically, the number of male patients included in this study is greater than that of female patients. Previous studies also reported a high prevalence of autism and ADHD in males (Ayano et al, 2020;Morales-Hidalgo et al, 2018;Özerk & Cardinal, 2020). Second, we did not assess the severity of the children's illnesses.…”
Section: Limitationsmentioning
confidence: 91%
“…Specifically, the number of male patients included in this study is greater than that of female patients. Previous studies also reported a high prevalence of autism and ADHD in males (Ayano et al, 2020;Morales-Hidalgo et al, 2018;Özerk & Cardinal, 2020). Second, we did not assess the severity of the children's illnesses.…”
Section: Limitationsmentioning
confidence: 91%
“…The prevalence of ADHD is between 5 and 7% for children and between 3 and 5% for adults [5]. According to systematic review and meta-analysis, prevalence of ADHD among school-aged children and adolescent vary from 2.2% to 17.8% worldwide [6]. According to epidemiological studies, ADHD in children is thought to continue in 50-80% of cases in adolescence and adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Attention deficit hyperactivity disorder (ADHD) mainly manifests as inattention, and/or hyperactivity and impulsivity [ 1 ] ; these behaviors appear on children under 12, and continues to adulthood [ 2 ] ; it affects 2.2% to 17.8% of children and youth, being the most common neurodevelopmental disorder. [ 3 ] Among children with ADHD, approximately one-third persists to adulthood. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%